Failure mechanism and characteristics of Nantang village basalt landslide induced by excavation and rainfall in Leibo County, Sichuan, China. Issue 6 (October 2021) - Feng, Wenkai; Yin, BaoGuo; Yi, Xiaoyu; Bai, Huilin; Dun, Jiawei; Zeng, Xiushu; Deng, Pengcheng
Abstract: Emeishan basalts are widely distributed in Southwest China, where several large-scale sliding disasters occurred in recent years. At about 5:00 am on July 2, 2017, a high-elevation basalt landslide occurred on the slope of Dongbiangou in Nantang Village, Nantian Township, Leibo County, Sichuan Province, forming a deposit with a volume of about 563.0 × 10 4 m 3 and burying houses, roads, and farmland. On the basis of a large number of geological surveys and engineering geological investigations on the disaster site, the formation mechanism and process were revealed by means of remote sensing satellite, unmanned aerial vehicle (UAV) aerial shot, and synthetic aperture radar on the ground, among other technical means. The results show that the weathered and broken basaltic rock mass and argillitization zone are the internal landslide causes, while the saturated water loading and infiltration softening caused by continuous rainfall and the disturbance of highway cutting slope are the external causes. The in-depth study of the formation mechanism and formation process of the Nantang landslide shows that the weathered and fragmented basalt slope should pay attention to interception and drainage measures and support measures during the construction and prevention process, to reduce the influence of water and human excavation on slope stability.